Association between child maltreatment and central sensitivity syndromes: a systematic review protocol. Issue 2 (3rd February 2019) - Chandan, Joht Singh; Thomas, Tom; Raza, Karim; Bandyopadhyay, Siddhartha; Nirantharakumar, Krishnarajah; Taylor, Julie
Abstract : Introduction: A growing body of evidence is identifying the link between a history of child maltreatment and a variety of adverse health outcomes ultimately leading to significant social and healthcare burden. Initial work has identified a potential association between child maltreatment and the development of a selection of somatic and visceral central sensitivity syndromes: fibromyalgia, chronic fatigue syndrome, temporomandibular joint disorder, chronic lower back pain, chronic neck pain, chronic pelvic pain, interstitial cystitis, vulvodynia, chronic prostatitis, tension-type headache, migraine, myofascial pain syndrome, irritable bowel syndrome and restless legs syndrome. Methods and analysis: Primary electronic searches will be performed in the Embase, MEDLINE, PubMed, Scopus, PyscINFO, CINAHL and Cochrane Library databases and a number of Grey Literature sources including child protection and paediatric conference proceedings. Following independent screening of studies by two review authors, the Preferred Reporting Items for Systematic Reviews and Meta-Analyses template will be used to aid extraction. A meta-analysis will be conducted on the included case-control and cohort studies. The Newcastle-Ottawa grading system will be used to assess the quality of included studies. Results will be expressed as pooled ORs for binary data and mean differences for continuous data. Ethics and dissemination: Ethics approval will not be required. The final results of the review and meta-analysis will be submitted for peer-review publication and also disseminated at relevant conference presentations. PROSPERO registration number: CRD42018089258.